Acid-Base Disorders in Patients with Chronic Obstructive Pulmonary Disease: A Pathophysiological Review. (1st February 2012) - Bruno, Cosimo Marcello; Valenti, Maria
Abstract : The authors describe the pathophysiological mechanisms leading to development of acidosis in patients with chronic obstructive pulmonary disease and its deleterious effects on outcome and mortality rate. Renal compensatory adjustments consequent to acidosis are also described in detail with emphasis on differences between acute and chronic respiratory acidosis. Mixed acid-base disturbances due to comorbidity and side effects of some drugs in these patients are also examined, and practical considerations for a correct diagnosis are provided.